STRATEGI SEKOLAH DALAM PENERAPAN PROGRAM PENGEMBANGAN BUDAYA DI SD NEGERI NGRUKEMAN KABUPATEN BANTUL - Safira Maulia; Mahilda Dea Komalasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The school’s strategy in implementing cultural development programs at SD Negeri Ngrukeman, Bantul Regency serves as an effort to preserve local culture while simultaneously shaping students’ character. The background of this study arises from the challenges of globalization, which have gradually eroded traditional cultural values, making it necessary for schools to function as agents of cultural preservation. This research aims to describe the strategies used in cultural development, the forms of cultural activities implemented, as well as the supporting and inhibiting factors faced by the school. The study employed a descriptive qualitative approach with data collected through interviews, observations, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, and were validated through source and technique triangulation. The findings indicate that the school implements cultural development strategies through habituation of positive values (5S: smile, greet, salute, polite, courteous), daily prayers, cleanliness routines, teacher modeling, integration of cultural values into classroom learning, cultural-based environmental conditioning, and various cultural activities such as karawitan, traditional dance, Friday Legi religious gatherings, and cultural parades. Supporting factors include strong commitment from school stakeholders, community involvement, and enthusiastic student participation. Meanwhile, challenges encountered include limited funding, insufficient cultural facilities, time constraints, and varying levels of student interest. Overall, the implementation of the cultural development program at SD Negeri Ngrukeman has proven to positively influence students’ character formation, improve their appreciation of local culture, and strengthen the school’s cultural identity. These findings demonstrate that well-planned and collaborative cultural strategies can serve as a vital foundation for character education and the preservation of local culture in the era of modernization.